Time tracking and comparison of genetic counseling tasks in inpatient and outpatient settings. - Osborne, Alexandra; Bland, Emily Magness; Diamonstein, Callie; Fishler, Kristen (Journal of Genetic Counseling, 2025)
Genetic counselors (GCs) practice in critical care settings. Some GCs have full‐time inpatient roles, while most GCs who see inpatients do so as needed or on a rotating schedule in addition to seeing patients in an outpatient setting. Few studies have tracked and compared the amount of time it takes GCs to perform tasks in the inpatient and outpatient settings. Genetic counselors were invited to participate in this study via the National Society of Genetic Counselors research listserv. Participants completed an online survey asking how their role is structured and what types of support are available to them while seeing inpatients. They also performed time tracking for 16 tasks known to be associated with inpatient and/or outpatient care via RedCap. These tasks include direct patient care, care coordination, and other tasks which encapsulate a new patient encounter from beginning to end. Forty‐two inpatient encounters and 26 outpatient encounters were analyzed. The total average time spent on an inpatient consult (3 h and 38.5 min) was significantly higher than the time spent on an outpatient consult (2 h and 24.7 min; p < 0.05). Individually, genetic counselors spent significantly more time on the following tasks in an inpatient setting: direct follow‐up encounters, multidisciplinary team communication, results disclosure encounters, results disclosure documentation, traveling, and waiting. Follow‐up encounters, traveling, and waiting happen almost exclusively in inpatient settings. Short answer prompts regarding structure of GC role and available support revealed themes including lack of inpatient role structure, challenges with balancing between inpatient and outpatient tasks, and varied institutional support. These results promote further discussion about how to support GCs who see inpatients as these roles expand. Some suggestions include increased FTE/protected time and/or GCA support specific to the inpatient role.